2022
DOI: 10.1038/s41467-022-28439-w
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium hydride enabled enantioselective intermolecular C–H silylation to access acyclic stereogenic Si–H

Abstract: The tremendous success of stereogenic carbon compounds has never ceased to inspire researchers to explore the potentials of stereogenic silicon compounds. Intermolecular C–H silylation thus represents the most versatile and straightforward strategy to construct C–Si bonds, however, its enantioselective variant has been scarcely reported to date. Herein we report a protocol that allows for the enantioselective intermolecular C–H bond silylation, leading to the construction of a wide array of acyclic stereogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 77 publications
0
14
0
2
Order By: Relevance
“…In recent years, enantioselective construction of silicon-stereogenic silanes has received increasing attention in organic synthesis given that these non-natural chiral silanes can serve as versatile chiral auxiliaries, reagents, building blocks, and catalysts or ligands. Among the many elegant approaches, rhodium-catalyzed desymmetrization of prochiral dihydrosilanes or tetraorganosilanes have been the focus of the most attention and have delivered a number of new transformations giving rise to various silicon-stereogenic silanes. In most cases, the discrimination of a Si–H or a Si–C bond is generally enabled by the chiral-Rh­(I)-catalyst-mediated desymmetric oxidative addition, which subsequently delivers the crucial chiral Rh–Si intermediate to proceed further stereospecific transformation, thereby furnishing the desired silicon-stereogenic silane products (Scheme b, top). , In view of the current state of the art for the Rh-catalyzed desymmetrization of prochiral dihydrosilanes or tetraorganosilanes, as well as the challenge for the access of silicon-stereogenic silanols, we questioned whether we could develop a new catalytic approach toward enantioenriched silanols via the desymmetrization of prochiral silanediols (Scheme a, right). Practically, unlike their carbon analogues, silanediols are easy to access with reasonable stability.…”
mentioning
confidence: 99%
“…In recent years, enantioselective construction of silicon-stereogenic silanes has received increasing attention in organic synthesis given that these non-natural chiral silanes can serve as versatile chiral auxiliaries, reagents, building blocks, and catalysts or ligands. Among the many elegant approaches, rhodium-catalyzed desymmetrization of prochiral dihydrosilanes or tetraorganosilanes have been the focus of the most attention and have delivered a number of new transformations giving rise to various silicon-stereogenic silanes. In most cases, the discrimination of a Si–H or a Si–C bond is generally enabled by the chiral-Rh­(I)-catalyst-mediated desymmetric oxidative addition, which subsequently delivers the crucial chiral Rh–Si intermediate to proceed further stereospecific transformation, thereby furnishing the desired silicon-stereogenic silane products (Scheme b, top). , In view of the current state of the art for the Rh-catalyzed desymmetrization of prochiral dihydrosilanes or tetraorganosilanes, as well as the challenge for the access of silicon-stereogenic silanols, we questioned whether we could develop a new catalytic approach toward enantioenriched silanols via the desymmetrization of prochiral silanediols (Scheme a, right). Practically, unlike their carbon analogues, silanediols are easy to access with reasonable stability.…”
mentioning
confidence: 99%
“…Based on their previous studies, in 2022, the He group published a Rh(I)-catalyzed intermolecular asymmetric C−H silylation of silacyclobutanes with heteroarenes using MeO-Biphep (S)-L4c as the optimal chiral ligand, yielding various chiral acyclic monohydrosilanes 170 in good results (up to 84% yield and 96% ee, Scheme 25b). 134 Then, a possible mechanism was proposed. The reaction proceeds with the coordination of thiophene to the Rh−H catalyst (171) 135 The presence of NBE-OMe (5-(methoxymethyl)bicyclo-[2.2.1]hept-2-ene), as a bulky hydrogen acceptor, could accelerate the dehydrogenative C−H silylation process.…”
Section: Rh(i)-catalyzed Asymmetric C−h Functionalization Reactions W...mentioning
confidence: 99%
“…In 2022, the He group reported another rhodium-catalyzed enantioselective C-H silylation of thiophene derivatives 72 using silacyclobutanes 71 as prochiral silanes (Scheme 19). 31 It was observed that while C3-substituted or unsubstituted thiophenes resulted in high stereoselectivity, substitution at the C2 position reduced the stereoselectivity of the reaction. This can be explained by the fact that the C2 substitution prevents the proper coordination of the S atom with the rhodium-catalyst.…”
Section: Special Topic Synthesismentioning
confidence: 99%